IMPROVEMENT OF STRUCTURAL HEREDITY IS A RESERVE OF THE SILUMINS CHARACTERISTICS IMPROVEMENT - E. I. Marukovich; V. Ju. Stetsenko (Литьë и металлургия)
The technology of the structure heredity improvement, which is a perspective and efficient way of improvement of the silumins ingots characteristics, is developed.